Evaluation of TOEFL preparation course program to improve students’ test score - Mega Selvi Maharani; Nur Hidayanto Pancoro Setyo Putro (Graduate School, Universitas Negeri Yogyakarta, 2021)
This research was conducted to evaluate the management program in English village, maintain the implemented program, and increase program quality. The method used in this study was descriptive qualitative and quantitative research. The model evaluation used was CIRO (Context, Input, Reaction, and Outcome) by War, Bird, and Rackman. The subject of this research were 30 students, four tutors, and a program director. Interview, survey, and observation were used for collecting the data. The analyzed quantitative data used descriptive percentages, and qualitative data used condensation, data exposure, conclusion drawing, and verification. The results of this study show that (1) context in this study considered to participant needed which synchronized to the standard implementation of the TOEFL real test and national standard. (2) input has been provided and is well prepared, including program plan, tutor qualification, for admission of course participants, and facilities. (3) Reaction of the participants' satisfaction was in the satisfactory category, and the participant's assessment reaction of the TOEFL program implementation process was in the very good category. (4) Outcome obtained by course participants in the TOEFL scoring has not increased significantly; it has even decreased during the last test.